Predictor of depressive symptoms among foundation students in Universiti Putra Malaysia - Lubaton, Clarisha; Madon, Zainal (Human Resource Management Academic Research Society, 2022)
This study examines the main factor of depressive symptoms among foundation students in Universiti Putra Malaysia. Through the cluster sampling technique, 345 students were involved in this study. The foundation students were assessed by a set of self-administered questionnaires of Sleep Quality Scale (Hyeryeon Yi, Kyungrim Shin & Chol Shin, 2006), Educational Stress Scale for Adolescent (Sun, Jiandong, Dunne, Michael, Hou, Xiang-Yu, Xu & Ai-qiang, 2011), Multidimensional Scale of Perceived Social Support (Zimet et al., 1988) and The Beck Depression Inventory-II (Beck, 1961). The results revealed that academic stress is prominent in predicting depressive symptoms among foundation students (?= 0.403, p= 0.000). The results of this study proved the transitions from high schools to tertiary institutions had challenged the foundation students to adapt to the new academic grading, projects and assignments, and lifestyle. It is suggested that foundation students need to master their time management to avoid unnecessary stressors. To generalize these findings, future studies should consider a larger sample size comprising foundation students from public and private universities to improve the accuracy and reliability of the result and provide more significant generalizations.